2011
DOI: 10.1590/s0103-05822011000100003
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à hipotermia durante o transporte intra-hospitalar em pacientes internados em Unidade de Terapia Intensiva Neonatal

Abstract: OBJETIVO: Determinar a frequência e os fatores associados à ocorrência de hipotermia em transportes intra-hospitalares de pacientes internados em uma unidade neonatal de cuidados intensivos. MÉTODOS: Estudo transversal aninhado em uma coorte prospectiva de crianças submetidas a transportes intra-hospitalares realizados por uma equipe treinada de janeiro de 1997 a dezembro de 2008 na unidade de cuidados intensivos de um hospital público universitário. Foram excluídos os transportes de pacientes com mais de um a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In a study on intra-hospital transfers it was revealed that even during short trips, the consequences for the NB health can be significant. They can develop hypothermia as the main complication followed by cardiac frequency disorders,, arterial pressure, respiratory frequency and oxygenation alterations (7) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on intra-hospital transfers it was revealed that even during short trips, the consequences for the NB health can be significant. They can develop hypothermia as the main complication followed by cardiac frequency disorders,, arterial pressure, respiratory frequency and oxygenation alterations (7) .…”
Section: Resultsmentioning
confidence: 99%
“…A NICU is a technological environment in which professional work and technological progress are aimed at the NB recovery. In these units, in which many medical procedures are performed by different professionals, there is a tendency for thermoirregularities due to the clinical instability of some assisted newborns (7) .…”
Section: Descriptoresmentioning
confidence: 99%
“…24 Transportar um RN assegurando a manutenção da termorregulação evita alterações da frequência cardíaca, da pressão arterial, da frequência respirató-ria e da oxigenação. 25 Desta forma, acredita-se que utilizar incubadora de parede dupla durante o transporte é fundamental para assegurar transporte mais eficaz. Transporte inter-hospitalar de recém-nascido crítico Medicina (Ribeirão Preto) 2015;48(6): 610-18 http://www.revistas.usp.br/rmrp / http://revista.fmrp.usp.br A utilização de colchão térmico para garantir a termorregulação do RN com peso <1500 gramas foi sugerida como uma alternativa a ser introduzida no transporte inter-hospitalar de neonatos de baixo peso.…”
Section: Condutas Organizacionais Realizadas No Referênciasunclassified